2018
DOI: 10.3201/eid2406.171965
|View full text |Cite
|
Sign up to set email alerts
|

Novel Parvovirus Related to Primate Bufaviruses in Dogs

Abstract: A novel protoparvovirus species, related genetically to human bufaviruses, was identified in dogs with respiratory signs. The canine bufavirus was distantly related to the well-known canine protoparvovirus, canine parvovirus type 2, sharing low amino acid identities in the nonstructural protein 1 (40.6%) and in the capsid protein 1 (33.4%). By screening collections of fecal, nasal, and oropharyngeal samples obtained from juvenile dogs (<1 year of age), canine bufavirus DNA appeared as a common component of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(138 citation statements)
references
References 46 publications
(63 reference statements)
5
125
3
Order By: Relevance
“…Novel protoparvoviruses were identified recently during an outbreak of canine infectious respiratory disease (CIRD) that occurred in a litter of mixed-breed 5-month-old puppies in Italy [3]. Also, by screening collections of faecal and respiratory specimens obtained from juvenile dogs, the virus was detected in stool samples of dogs with or without enteric disease and in nasal and oropharyngeal swabs of dogs with CIRD.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Novel protoparvoviruses were identified recently during an outbreak of canine infectious respiratory disease (CIRD) that occurred in a litter of mixed-breed 5-month-old puppies in Italy [3]. Also, by screening collections of faecal and respiratory specimens obtained from juvenile dogs, the virus was detected in stool samples of dogs with or without enteric disease and in nasal and oropharyngeal swabs of dogs with CIRD.…”
Section: Introductionmentioning
confidence: 99%
“…Also, by screening collections of faecal and respiratory specimens obtained from juvenile dogs, the virus was detected in stool samples of dogs with or without enteric disease and in nasal and oropharyngeal swabs of dogs with CIRD. Analysis of the complete genome sequences of three strains (ITA/2015/297, HUN/2012/126 and HUN/212/22) [3] showed that a novel canine parvoviruses, designated canine bufaviruses (CBuVs), exhibited the highest sequence the identity in NS1 (66.9%-69.4% nucleotide [nt] and 47.2%-51.4% amino acid [aa]) and VP1 (66%-68.2% nt and 62.5%-67.2% aa) regions to human and non-human primate bufaviruses (BuVs) (Primate protoparvovirus 1 and Primate protoparvovirus 2) [4][5][6], while identity to the well-known CPV-2 (Carnivore protoparvovirus 1) was 56% nt and 40.6% aa in NS1 and 42.6% nt and 33.4% aa in VP1. According to the criteria established by the International Committee on Taxonomy of Viruses (ICTV) for classification of parvoviruses into the same species (cutoff > 85% aa sequence identity in the NS1 protein), the canine protoparvovirus may be considered a member of a new species within the genus Protoparvovirus, for which he name "Carnivore protoparvovirus 2" is proposed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel protoparvovirus, distantly related to canine parvovirus 2, was identified in young dogs with respiratory disease that tested negative to a panel of respiratory pathogens. The virus was also detected in collections of respiratory and enteric swabs, and its presence was significantly associated only in young animals (,6 months) with respiratory disease (Martella et al, 2018).…”
Section: Viral Metagenomics and Discovery Of New Viruses In Pets 28mentioning
confidence: 98%